BOARDROOM DIVERSITY AND ESG PERFORMANCE: EXAMINING NIGERIAN FIRMS’ COMMITMENT TO SUSTAINABILITY A CASE STUDY OF THE NIGERIAN BANKING SECTOR - Jide, Ibikunle (Journal Of Islamic Finance And Accounting Research, 2025)
Environmental, Social, and Governance (ESG) considerations have become central to corporate governance, financial sustainability, and long-term business success. As global investors and regulators emphasize sustainable business practices, companies are increasingly required to integrate ESG principles into their corporate strategies and financial disclosures. This study examined the impact of boardroom diversity on ESG performance in Nigerian banks, focusing on gender diversity, board size, independent directors, board tenure, and educational background. Using secondary data from annual reports and sustainability disclosures of five top-tier commercial banks between 2017 and 2023, this study evaluated the relationship between board composition and ESG outcomes. The findings indicated that while boardroom diversity is an essential governance mechanism, its direct effect on ESG performance is statistically weak. Gender diversity showed a positive but insignificant impact on ESG scores, while board size and the proportion of independent directors exhibited negative relationships. Board tenure, although positively associated with ESG performance, lacked statistical significance. These results suggested that beyond demographic diversity, board effectiveness in driving ESG integration depends on regulatory enforcement, corporate policies, and sustainability expertise.